ANALISIS YURIDIS TERHADAP PEMBAYARAN ZAKAT DALAM PENGADAAN PAJAK PENGHASILAN - SELFIANA EFRIDA LUBIS (PREMISE LAW JURNAL, 2014)
ABSTRACT Most of the Indonesian taxpayers are Muslims who have another obligation which has to be done, to pay zakat (obligation to contribute to those in need or to religious activities). Law No. 36/2008 on PPh (income tax), Law No. 23/2011 on the Management of Zakat, and the Regulation of Director General of Tax No. PER-6/PJ/2011 on the Implementation of Payment and Writing the Evidence of Zakat Payment or Obligatory Religious Contribution which can be Deducted from Gross Income regulate that the payment of zakat as the deduction of PKP (taxable earnings in PPh). However, many individual taxpayers who are Muslims or Muzakis have not paid their zakat as the deduction of PKP in PPh. The payment of zakat can taken from the amount of PPh by deducting Net Income. All types of zakat mal (charity given because one has more than enough) are paid at BAZ/LAZ (Charitable Institution) which is established and validated by the Government in which BSZ (Evidence of Payment) is attached in the SPT report of annual WP(Taxpayer). Keywords : Income Tax, Taxpayers, Zakat.